Enhance the Quality of Medical Liquid Waste via Agitation Utilizing Hydrochloric Acid Activator in conjunction with Bamboo Activated Carbon - Setyarini, Putu Hadi; Felixanto Cendikia,; Achmad As’ad Sonief, (International Journal of Integrated Engineering, 2024)
The proper treatment of medical waste, which originates from various medical procedures, plays a vital role in protecting the environment and promoting human health. One potential strategy for improving the quality of medical waste is the utilization of the adsorption process for the goal of purification. The implementation of a biomass-derived activated carbon medium can enhance the execution of this technique. The aim of this study is to investigate the changes in the morphological and chemical properties of activated carbon derived from Gigantochloa apus (GA) and Bambusa vulgaris (BV) after being exposed to medical waste. The chemical activation technique is performed using a hydrochloric acid (HCl) solution with a concentration of 0.1 M. The length of the drying procedure has an impact on the surface properties and pore development of activated carbon, which has the potential to enhance its capacity for adsorbing chemicals in liquid medical waste. There exists a positive association between the length of agitation and the pH value, resulting in an augmentation of ion absorption. The activated carbon known as BV exhibits a greater carbon content in comparison to GA activated carbon, resulting in a reduction in Total Dissolved Solids (TDS) within treated wastewater. The phenomenon of agitation serves to promote the contact between the adsorbent and adsorbate, hence leading to the reinforcement of Van der Waals forces. BV exhibits a greater absorption capacity in comparison to GA